Bioluminescence resonance energy transfer (BRET) imaging of protein-protein interactions within deep tissues of living subjects - Dragulescu-Andrasi, Anca; Chan, Carmel T; De, Abhijit; Massoud, Tarik F; Gambhir, Sanjiv S (Proceedings of the National Academy of Sciences - PNAS, 2011)
Identifying protein-protein interactions (PPIs) is essential for understanding various disease mechanisms and developing new therapeutic approaches. Current methods for assaying cellular intermolecular interactions are mainly used for cells in culture and have limited use for the noninvasive assessment of small animal disease models. Here, we describe red light-emitting reporter systems based on bioluminescence resonance energy transfer (BRET) that allow for assaying PPIs both in cell culture and deep tissues of small animals. These BRET systems consist of the recently developed Renilla reniformis luciferase (RLuc) variants RLuc8 and RLuc8.6, used as BRET donors, combined with two red fluorescent proteins, TagRFP and TurboFP635, as BRET acceptors. In addition to the native coelenterazine luciferase substrate, we used the synthetic derivative coelenterazine-v, which further red-shifts the emission maxima of Renilla luciferases by 35 nm. We show the use of these BRET systems for ratiometric imaging of both cells in culture and deep-tissue small animal tumor models and validate their applicability for studying PPIs in mice in the context of rapamycin-induced FK506 binding protein 12 (FKBP12)-FKBP12 rapamycin binding domain (FRB) association. These red light-emitting BRET systems have great potential for investigating PPIs in the context of drug screening and target validation applications.